2017
DOI: 10.1080/00295450.2017.1336029
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of the Department of Energy’s Advanced Demonstration and Test Reactor Options Study

Abstract: An assessment of advanced reactor technology options was conducted to provide a sound comparative technical context for future decisions by the Department of Energy (DOE) concerning these technologies. Strategic objectives were established that span a wide variety of important missions and advanced reactor technology needs were identified based on recent Department of Energy and international studies. A broad team of stakeholders from industry, academia and government was assembled to develop a comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The concept of HTGRs, or known as Very-High-Temperature Gas-Cooled Reactor (VHTR), was promulgated in the Generation IV technology roadmap in 2001 as one of the Next Generation Nuclear Power Plant (NGNP) designs [3]. Researchers have concluded that HTGRs have a high technology-readiness-level, which will enable near-term deployment in flexible energy missions [4,5]. Beyond electricity, HTGRs provide another impactful way to increase the application of nuclear energy and reduce greenhouse gas emissions by substituting high-quality nuclear-generated steam for fossil fuels in energy-intensive industrial applications given their high operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of HTGRs, or known as Very-High-Temperature Gas-Cooled Reactor (VHTR), was promulgated in the Generation IV technology roadmap in 2001 as one of the Next Generation Nuclear Power Plant (NGNP) designs [3]. Researchers have concluded that HTGRs have a high technology-readiness-level, which will enable near-term deployment in flexible energy missions [4,5]. Beyond electricity, HTGRs provide another impactful way to increase the application of nuclear energy and reduce greenhouse gas emissions by substituting high-quality nuclear-generated steam for fossil fuels in energy-intensive industrial applications given their high operating temperatures.…”
Section: Introductionmentioning
confidence: 99%